PENGARUH CAPITAL ADEQUACY RATIO (CAR), SUKU BUNGA (BI RATE), DAN NILAI TUKAR TERHADAP LOAN TO DEPOSIT RATIO (LDR) PADA PT BANK NEGARA INDONESIA TBK, DI INDONESIA PERIODE 2001-2019 - Waruwu Luther Martin; Richard Rahmat; Darmayuda Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze how much influence the Capital Adequacy Ratio (CAR), Interest Rate (BI Rate), and Exchange Rate have on the Loan To Deposit Ratio (LDR) at PT Bank Negara Indonesia Tbk, in Indonesia. This study uses independent variables consisting of Capital Adequacy Ratio (CAR), Interest Rate (BI Rate), and Exchange Rate with the dependent variable is Loan To Deposit Ratio (LDR). The data used in this study is annual data from 2001-2019. The analytical method used is descriptive quantitative and processed using SPSS Version 24. The test results show that the Capital Adequacy Ratio (CAR) has no effect on the Loan To Deposit Ratio (LDR) while the interest rate (BI rate) has a significant negative effect and the exchange rate has a positive effect. significant to Loan To Deposit Ratio (LDR)Keywords : Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Interest Rate (BI Rate), and Exchange Rate